Amorphization of Drugs for Transdermal Delivery-a Recent Update - Bappaditya Chatterjee; Abhishek Reddy; Moushami Santra; Sandile Khamanga (MDPI AG, 2022)
Amorphous solid dispersion is a popular formulation approach for orally administered poorly water-soluble drugs, especially for BCS class II. But oral delivery could not be an automatic choice for some drugs with high first-pass metabolism susceptibility. In such cases, transdermal delivery is considered an alternative if the drug is potent and the dose is less than 10 mg. Amorphization of drugs causes supersaturation and enhances the thermodynamic activity of the drugs. Hence, drug transport through the skin could be improved. The stabilization of amorphous system is a persistent challenge that restricts its application. A polymeric system, where amorphous drug is dispersed in a polymeric carrier, helps its stability. However, high excipient load often becomes problematic for the polymeric amorphous system. Coamorphous formulation is another approach, where one drug is mixed with another drug or low molecular weight compound, which stabilizes each other, restricts crystallization, and maintains a single-phase homogenous amorphous system. Prevention of recrystallization along with enhanced skin permeation has been observed by the transdermal coamorphous system. But scalable manufacturing methods, extensive stability study and in-depth in vivo evaluation are lacking. This review has critically studied the mechanistic aspects of amorphization and transdermal permeation by analyzing recent researches in this field to propose a future direction.